Interfaith Religious Harmony in Besowo Kediri Landscape - Khainuddin, Khainuddin; Huda, M Thoriqul (Tribakti: Jurnal Pemikiran Keislaman, 2022)
Religious people realize the importance of maintaining religious harmony, tolerance in religion is needed in conditions of heterogeneous community areas. Theologically religion teaches its people to be tolerant in religion, this is reflected in the various lives in Besowo village, Kediri, where conditions of religious life run in harmony and peace. This study will look comprehensively at the portrait of the relationship between diverse people in Besowo, the factors that encourage the creation of religious harmony, the role of religious leaders and public perceptions in seeing the era of globalization in the eyes of religious harmony. The results showed that the Besowo community had built religious harmony from generation to generation, culture became one of the adhesive fields in inter-religious relations, while religious leaders played a role in encouraging the development of moderate religious attitudes both in mindset and behavior, in addition to facing the era of globalization. Global society is required to be wiser and behave positively on social media.